3.B. Workshop: Monitoring the wider impacts of COVID-19 on population health. (20th October 2021) - ,; ,
Abstract:  : COVID-19 has clearly shown that a structured European mechanism for COVID-19 exchange to organize and share accurate information between countries is urgently needed, especially in the area of population health, to inform decision-makers, researchers and the public. The implications of the COVID-19 pandemic reaches far beyond the immediate mortality and morbidity aspects caused by the virus directly. There are many indirect effects of the outbreak that affect health through various pathways. This includes secondary consequences of COVID-19 on long-term health and wellbeing, including consequences due to delayed prevention, diagnosis, and medical treatment. Within the Population Health Information Research Infrastructure (PHIRI), best available evidence for research on health and well-being of populations as impacted by COVID-19 is generated and facilitated by a research infrastructure on population health. It supports research across Europe through the identification, access, assessment and reuse of population health and non-health data to underpin public health policy decisions. PHIRI is a practical use case and lays the foundation for ultimately developing a Distributed Infrastructure on Population Health (DIPoH). The joint workshop aims to raise the awareness and ensure a better understanding of the complexity of the wider effects of COVID-19 on population health across Europe. To provide insights of how the wider impacts of the COVID-19 pandemic could be assessed, tools and methodological approaches gained within PHIRI and WHO are presented. Knowledge and expertise developed across Europe is shared in this workshop which is key to supported countries to address the COVID-19 crisis. The workshop will begin with a presentation on monitoring the wider effects of COVID-19 on population health as set out by the WHO. This will be followed, after a short introduction on PHIRI, by three presentations which highlight key activities of assessing the wider impact of COVID-19 by PHIRI. The first on research methodologies evaluated across Europe to assess the direct and indirect impacts of COVID-19 on population wellbeing, morbidity and mortality across European countries. The second at COVID-19 impacts in specific subgroups and risk settings by conducting research through four use cases of immediate relevance. This facilitates research by making scalable, reproducible methods available within PHIRI. Finally, the third on insights in possible future health impacts of the COVID-19 outbreak by foresight and modelling scenarios for national situations as well as the provision of research capacity to strengthen the evidence-informed policy decisions on direct/indirect effects of COVID-19 will be presented. Exchange with the audience will facilitate knowledge and opinion exchange through an interactive Mentimeter poll during the session, to offer the delegates to share, in real time, their perspectives on selected questions based on the four presentations. Key messages: The main outputs will support European countries to develop tools and methodologies for measuring the wider impacts of COVID-19 on population health within and across countries. The results will support the exchange of knowledge and expertise across Europe by facilitating insights in the assessment of direct and indirect effects of COVID-19 on population health.